Prevalence and Multilocus Genotyping Analysis of Cryptosporidium and Giardia Isolates from Dogs in Chiang Mai, Thailand - Tangtrongsup, Sahatchai (Vet Sci, 2017)
The occurrence and zoonotic potential of Cryptosporidium spp. and Giardia duodenalis isolated from dogs in Chiang Mai, Thailand were determined. Fecal samples were collected from 109 dogs between July and August 2008. Cryptosporidium spp. infection was determined by immunofluorescent assay (IFA), PCR assays that amplify Cryptosporidium heat-shock protein 70 kDa (hsp70), and two PCR assays that amplify a small subunit-ribosomal RNA (SSU-rRNA). Giardia duodenalis infection was identified using zinc sulfate centrifugal flotation, IFA, and four PCR assays that amplify the Giardia glutamate dehydrogenase (gdh), beta-giardin (bg), and generic and dog-specific assays of triosephosphate isomerase (tpi) genes. Overall prevalence of Cryptosporidium spp. and G. duodenalis was 31.2% and 45.9%, respectively. Sequence analysis of 22 Cryptosporidium-positive samples and 21 Giardia-positive samples revealed the presence of C. canis in 15, and C. parvum in 7, G. duodenalis Assemblage C in 8, D in 11, and mixed of C and D in 2 dogs. Dogs in Chiang Mai were commonly exposed to Cryptosporidium spp. and G. duodenalis. Cryptosporidium parvum can be isolated from the feces of dogs, and all G. duodenalis assemblages were dog-specific. Dogs could be a reservoir for a zoonotic Cryptosporidium infection in humans, but further studies will be required to determine the clinical and zoonotic importance.